A consolidated review on stem cell therapy for treatment and management of Alzheimer's disease - Faizan Ahmad; Punya Sachdeva (Aging Medicine, 2022)
Abstract Alzheimer's disease (AD) is one of the most common forms of dementia and affects around 50 million people around the globe. AD is diagnosed mainly through imaging techniques and to date only five drugs are approved for management of AD but no promising treatment is available for AD. So in this review, we are focusing on stem cell therapy for AD. This review will cover all stem cells like mesenchymal stem cells, embryonic stem cells, induced pluripotent stem cells, and neural stem cells. Clinical trials of AD have also been discussed. Finally, limitations of stem cells are discussed with ongoing clinical trials, and in the future stem cell therapy can be used for treatment of AD.